Currency demand, the underground economy, and, tax evasion - the case of Guyana - Faal, Ebrima (IMF [Washington]US, 2003)
Attempts to estimate the magnitude of, and changes to the underground economy in Guyana, as well as its adverse effect on tax collection during the period 1964-2000.